The Role of Product Belief in Mediating the Effect of Live Streaming and Consumer Ethnocentrism on Online Purchase Intention of Local Skincare for Men - Nuzul Hidayat; Sulhaini Sulhaini; Baiq Handayani Rinuastuti (Journal The Winners, 2026)
This study investigated how product belief mediates the effect of live streaming and consumer ethnocentrism on online purchase intentions for local male skincare products on TikTok. The male segment tends to be less targeted by marketers than the female segment, eventhough it has promising growth potential. Few studies focus on male consumers in the skincare category, leaving a gap in the understanding of their behavior. This research employs a causal associative design using a survey method. The population comprised young males aged 17-38 years, sampled purposively. Data analysis was performed using SmartPLS. Results show that live streaming significantly and positively impacts online purchase intention and product belief. Although consumer ethnocentrism positively influences product belief, its effect on purchase intention is not significant. Consumer ethnocentrism significantly enhances product belief, which in turn positively affects purchase intention. The combined impact of live streaming and consumer ethnocentrism on purchase intention, mediated by product belief, is also significant. These findings highlight the critical mediating role of product belief in the relationship between live streaming and consumer ethnocentrism and online purchasing behavior. Based on these findings, companies should focus more on building consumer trust in their products, particularly local products, to increase consumer online purchase intentions.